Oral Contract on the Sale and Purchase Transactions in the Traditional Market of Palangka Raya City - Muzalifah Muzalifah; Ali Sodiqin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The application of an oral contract in buying and selling transactions in Palangka Raya City is a form of contract adopted from Banjar culture. Even traditional market players in Palangka Raya City, in particular, interpret the oral contract as something that is very principle, so that they consider a contract invalid if it is not stated verbally. This article explores the question of why the oral contract in buying and selling in Palangka Raya City is still being applied and how the oral contract law is in buying and selling transactions in Palangka Raya City. This research is qualitative research with a phenomenological approach. This study found that the application of oral contracts in buying and selling transactions in Palangka Raya City originated from the habits of Banjar tribe traders who trade in Palangka Raya City. This habit, then, develops into the habit of the local community, so it becomes a necessity to be implemented. The law of the oral contract in the transaction is valid in terms of Islamic law and civil law because it fulfills the requirements and is in harmony with the contract in buying and selling and is carried out voluntarily, is based on the principle of freedom of contract. There is a balance of achievement, and has legal certainty so that it binds both parties. The existence of this oral contract shows the legitimacy of legal norms, religious norms, and customary norms.